FAKTOR-FAKTOR YANG BERKAITAN DENGAN DOMAIN KUALITAS HIDUP SISWA DENGAN GANGGUAN PENDENGARAN - Giovani Indah G.P; Ricky Yue; Yunisa Astiarani (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: Hearing problems in school-age children impact several aspects of their quality of life (QoL). This study aims to describe the presiding QoL domains in students with hearing problems and investigate factors related to their quality of life.Methods: A cross-sectional study design using a modification of the World Health Organization Quality of Life Abbreviation version (WHOQOL-BREF) applied in a special school for hearing-impaired students. The self-answered questionnaire was collected by the teacher, along with several questions of sociodemographic and community engagement. A descriptive analysis was conducted to describes the QoL domains on student's characteristics. The multivariate analysis was then performed to denotes the association between variables of interest and QoL domains.Results: A total of 34 students were enrolled in the study. The environment domain shows the highest scores (65.5±14), while social interaction is the lowest (51.7±10). The environment and the social interaction domains indicate a positive correlation with community engagement (p=0.04). A negative correlation was found between the environment domain and age (p=0.0001).Conclusion: Deaf-community engagement has a positif correlation with the environment and social interaction domain in the student's quality of life. The low social interaction scores specify the importance of community engagement in motivation and self-development. Special attention to older students needed to improve their adaptation ability in society and function normally